Analisis Kebijakan Pendidikan tentang Digitalisasi Perguruan Tinggi - Sirajuddin Saleh; Nurhandayani; Wahyuni; Sri Putri Mayanti; Andi Tanri Bulan; Alya Ashari F; Andang Subagyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Digitalization of higher education is a rapidly developing form of educational transformation in the information technology era. Digitalization policies are implemented to improve the quality of learning, administrative efficiency, and the competitiveness of higher education institutions at the national and international levels. This study aims to analyze educational policies regarding digitalization of higher education institutions, including the benefits, challenges, impacts, and implementation strategies. The method used in this article is a qualitative descriptive method with a literature review approach. The analysis shows that digitalization has a positive impact on learning flexibility, educational access, and the efficiency of academic services. However, several obstacles remain, such as limited infrastructure, low digital literacy, gaps in access to technology, and data security risks. Therefore, an integrated policy is needed through strengthening infrastructure, improving digital competencies, and developing a technology-based education system to ensure optimal digital transformation in higher education institutions. Keywords: Digitalization of Education, Higher Education, Educational Policy, Digital Transformation, Educational Technology